Antagonistic cultures or global stratification? Lessons of history and social analysis: the causes of tensions in multicultural societies - Drwęski, Bruno (Zakład Pedagogiki Społecznej Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
When we observe the history and heritage of great civilizations, we notice that we had almost always to do with civilizations we can define as "multicultural", even if such a concept did not exist in those times. Mesopotamia, Persia, Hellenistic States, and ancient Rome at the time of their splendour, Arab-Muslim empires during the Middle Ages, Mongol-Yuan Chinese empire, of Mongol Indies, Polish-Lithuanian-Ruthenian "Republic of the Two Nations", Soviet Union, United States - those are some examples of states and civilizations that, not taking into account our own opinions and feelings concerning their political regime or legitimacy, managed to have a strong influence on their development of human culture, art and political, social, ideological, theological, economical, scientific or legal culture.
Keywords: Europe; islam; crisis; orientalism; West